Design, development and metrological characterization of a low capacity precision industrial force transducer. (September 2015) - Kumar, Harish; Sharma, Chitra; Kumar, Anil; Arora, P.K.; Kumar, S.
Abstract: The paper discusses the development of the ring shaped force transducers for measurement of force in lower capacity to meet the industrial requirements with the increasing technological developments. A 50 N ring shaped force transducer for tension mode has been developed by studying the analytical and computational methods. The force transducer developed has been metrologically studied according to the calibration procedure based on the standard ISO 376 and uncertainty of measurement of the force transducer is found to be±0.10% ( k =2), while taking into account the relative uncertainty contribution due to necessary factors like repeatability, reproducibility, zero offset, interpolation, resolution and reversibility. The force transducer developed may further be studied for improvement of metrological performance and may suitably be developed for other lower capacities like 10 N, 20 N etc. The force transducer developed offers very economical alternative of complex shaped force transducers with simple design and manufacturing features. The force transducer developed may be proved very helpful in providing traceability to the user industries and calibration laboratories in the lower range of force measurement and serve as force transfer standard. Highlights: Ring shaped force transducer has been developed for capacity of 50 N. Force transducer is metrologically investigated according to the standard ISO 376. Force transducer offers economical alternative of complex and commercial force transducers. Force transducer developed is very useful for industrial and metrological applications.